Psychometric testing of the short version of the world health organization quality of life (WHOQOL-BREF) questionnaire among pulmonary tuberculosis patients in Taiwan - Chung Wei-Sheng; Lan Yu-Ling; Yang Ming-Chin (BMC, 2012)
Abstract Background Studies on the effects of tuberculosis on a patient's quality of life (QOL) are scant. The objective of this study was to evaluate the psychometric properties of the Taiwan short version of the World Health Organization Quality of Life (WHOQOL-BREF) questionnaire using patients with tuberculosis in Taiwan and healthy referents. Methods The Taiwanese short version of the WHOQOL-BREF was administered to patients with tuberculosis undergoing treatment and healthy referents from March 2007 to July 2007. Patients with tuberculosis (n = 140) and healthy referents (n = 130), matched by age, sex, and ethnicity, agreed to an interview. All participants lived in eastern Taiwan. Reliability assessments included internal consistency, whereas validity assessments included construct validity, convergent validity, and discriminant validity. Results More than half of these patients and referents were men (70.7% and 66.2%, respectively), and their average ages were 50.1 and 47.9 years, respectively. Approximately 60% of patients and referents were aboriginal Taiwanese (60.7% and 61.1%, respectively). The proportion with low socioeconomic status was greater for these patients. The internal consistency reliability coefficients were .92 and .93 for the patients and healthy referents, respectively. Exploratory factor analysis on the healthy referents displayed a 4-domain model, which was compatible with the original WHOQOL-BREF 4-domain model. However, for the TB patient group, after deleting 3 items, both exploratory and confirmatory factor analysis revealed a 6-domain model. Conclusion Psychometric evaluation of the Taiwan short version of the WHOQOL-BREF indicates that it has adequate reliability for use in research with TB patients in Taiwan. However, the factor structure generated from this TB patient sample differed from the WHO's original 4-factor model, which raised a validity concern to apply the Taiwan short version of the WHOQOL-BREF to Taiwanese TB patients. Future research recruiting another sample to revisit this validity issue must be conducted to determine the validity of the WHOQOL-BREF TW in patients with TB.